Parents’ knowledge, attitude and practice regarding childhood circumcision: a cross-sectional study in the central region of Sichuan, China - Zou, Bing; Tan, Chunlin; Deng, Rui; Chen, Qiang; Peng, Qiu; Xu, Dong; Gou, Yunpeng; Du, Yong; Li, Kangming; Chen, Zhili; Yang, Ping (Frontiers in Pediatrics, 2025)
IntroductionThis cross-sectional study aimed to explore parents’ knowledge, attitudes, and practices (KAP) regarding male circumcision (MC) for their children.MethodsA cross-sectional study was conducted among parents of male children under 18 years old in the central region of Sichuan, China, between September 2023 and January 2024 Questionnaires were distributed to collect demographic information and KAP scores.ResultsA total of 497 valid questionnaires were collected. The average knowledge score was 6.66 ± 2.34 (range: 0–10), attitude score was 38.04 ± 4.52 (range: 12–60), and practice score was 24.81 ± 3.49 (range: 6–30). Parents demonstrated highest awareness regarding the positive effects of MC on penis health, but showed lowest understanding of MC benefits for children with redundant prepuce or phimosis. Notably, 75% of parents indicated a willingness to have the procedure performed in the future. Multivariate analysis identified knowledge, attitude, and residence as independent factors associated with consent for childhood circumcision. Path analysis revealed positive influences from knowledge to attitude, knowledge to practice, and attitude to practice.ConclusionsThe study highlights the importance of targeted educational interventions to enhance parental understanding and decision-making regarding childhood MC. Educational programs can empower parents to make well-informed decisions considering both cultural and medical contexts.